Strengthening Awareness of Islamic Family Law Through Community-Based Education in Contemporary Era: A Study of the Yasin Nurul Hidayah Congregation, Kediri - Abdullah Affandi; Indana Zulfa; Abdulnasir Alsayd (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Purpose – This study aims to examine how community-based education initiatives can raise awareness of Islamic family law regarding gender roles, rights and obligations, and domestic relationships among the congregation of Yasin Nurul Hidayah in Kediri. Methods – The research used a Community-Based Research (CBR) approach, involving the congregation as active partners in every stage of the activity. A series of interventions were carried out in the form of seminars, participatory workshops, and legal consultations. Findings – The results of the study show that participants not only gained a better understanding of Islamic family law, but also the ability to apply the principles of Islamic family law in their daily lives. The integration of local cultural values into each activity strengthened the legitimacy of the program and fostered a sense of shared ownership. Overall, the participatory approach proved effective in changing individual awareness while shaping a more equitable, cooperative, and mutually respectful collective attitude in family life. Implications – These findings enrich the discourse on legal empowerment by emphasising the importance of participatory and contextual strategies in raising Islamic family legal awareness. This study emphasises that sustainable family harmony cannot rely solely on normative regulations. Originality - This study shows that community-based approaches can be an innovative pathway to strengthen family resilience while promoting social transformation.